Prospective Teachers’ Barriers in Field Practice Experience - Dessy Kurniasy; Zahratul Idami; Shafrida Wati; Sekar Ayu Lestari (PT ARRUS Intelektual Indonesia, 2023)
Teaching Practice Experience Program is one of the mandatory courses for all students of the faculty of education. This activity aims to provide real experience for students as prospective teachers. This study described prospective teachers' difficulties in practical teaching during their field practice experience program in Langsa, Aceh, Indonesia. This study applied a qualitative descriptive approach with a case study type of research. The participants were selected purposively. They were the seventh-semester students of the English Department who had conducted field practice experience consisting of 6 students. The data was collected through semi-structured interviews. The result revealed that among the barriers they encountered during their field practice experience were difficulties in facilitating a vibrant classroom atmosphere, teaching by using English, selecting and implementing appropriate methods or techniques, especially in teaching writing skills and challenges to execute lesson plans. Henceforth, this research contributes to enrich the literatures of field teaching practice and the barriers found, so it can be a valuable reference in the next research to provide the solution of the problems.